Anatomia Clavis et Clavus Medicinae Storia dell'Anatomia nell'Università di Cagliari - Trucas, Marcello (Storia e Memorie della Medicina e della Biologia, 2020)
Recurring in 2020 the 400th year since the founding of the University of Cagliari, the Authors have the dual ambition to make a scientific-cultural contribution to the University's celebrations and to enhance the role of Anatomy and its teaching in society and in the medical events that have accompanied the evolution of healthcare and medical culture in Cagliari and Sardinia.